Economizing the political: Workfare reform in strategic management mode - Hanna Ylöstalo; Lisa Adkins (SAGE PUBLICATIONS LTD, 2022)
The focus of this article is a recent round of workfare reform in Finland. Departing from many existing analyses of workfare, it focuses on issues of governance. Drawing on policy documents and interviews with key policy actors, it shows how this reform and attempts at implementation took place along the lines of a specific form of managerial governance, namely strategic governance, involving the enrolment of strategic management into policy making. The article details how this mode of policy making enabled an intensification and depoliticization of workfare policies via the replacement of political concerns with economic imperatives and in so doing contributed to the broader process of economization of the state. While the latter is often located as central to the project of neoliberalism, the practices through which it is instantiated often remain hazy. This article therefore contributes knowledge on how the process of the economization of the political operates in practice.